Genetic divergence between sub-accessions of the melon using molecular markers - Coelho de Amorim, Clisneide (Revista Ciência Agronômica, 2021)
The melon (Cucumis melo L.) is one of the most important horticultural crops in the northeast of Brazil. The characterisation of germplasm is an effi cient process for managing plant genetic resources, as it contributes to better conservation and improved use in breeding programs. In the present study, the genetic divergence between sub-accessions of the melon taken from traditional agriculture in the semi-arid region of Brazil was evaluated using ISSR and RAPD markers, verifying the level of agreement with the botanical classifi cation. Twenty-six sub-accessions preserved in the Active Germplasm Bank of Cucurbitaceae for the northeast of Brazil, located at Embrapa Semiárido in Petrolina, Pernambuco, were analysed. The binary matrix of the molecular data was used to obtain the genetic dissimilarities using the complement of the Jaccard index. The genetic dissimilarities were represented in dendrograms generated using the UPGMA method. Twenty-eight ISSR primers and 26 RAPD primers were polymorphic. A total of 686 fragments were obtained, of which 451 were polymorphic. The mean polymorphism of the RAPD markers was greater than that of the ISSR markers. The number of markers was considered suffi cient to accurately determine the genetic diversity. The ISSR dendrogram allowed the formation of three groups, the RAPD dendrogram, four groups, and the joint dendrogram, three groups. The study demonstrated the genetic variability between the sub-accessions, and the strong association between the characterisation made by the molecular markers and the taxonomic classifi cation of the genotypes under study.